The Comprehensive Complication Index in Ulcerative Colitis: A Comparison with the Clavien‒Dindo Classification - Yuki Horio; Motoi Uchino; Masataka Igeta; Kentaro Nagano; Kurando Kusunoki; Ryuichi Kuwahara; Toshiyuki Sato; Shinichiro Shinzaki; Hiroki Ikeuchi (Inflammatory Intestinal Diseases, 2024)
Introduction: The comprehensive complication index (CCI), which weights all postoperative complications according to severity and integrates them into a single formula, has been reported as a new evaluation system. We aimed to compare the CCI with the Clavien‒Dindo Classification (CDC) to patients with ulcerative colitis (UC). Methods: Patients who underwent initial surgery for UC from April 2012 to March 2020 were included. The patients were classified into a length of stay (LOS) >30 days group or an LOS ≤30 days group. We performed a multivariate analysis of risk factors for LOS >30 days in the model with the factors identified in the univariate analysis plus the CCI (the CCI model) and plus CDC (the CDC model). An ROC curve was used to test the difference in the area under the curve (AUC) between the CCI model and the CDC model. Results: The median LOS was 21 days (IQR: 16-29 days), and the rate of LOS >30 days was 119/588 (20.2%). In the CCI model, age at the time of surgery (OR=1.24, 95% CI 1.07-1.45, p=0.01), ASA score ≥3 (OR=1.94, 95% CI 1.00-3.76, p=0.04), and CCI (OR=1.07, 95% CI 1.05-1.09; p30 days. The AUC value of the CCI model (0.86) was significantly better in relation to LOS > 30 days than that of the CDC model (0.82) (p =0.02). Conclusion: The CCI was a better measure of LOS than was the CDC and was found to be a useful indicator in UC.